2018
DOI: 10.1186/s12883-018-1137-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of seizure semiology obtained from first-time seizure witnesses

Abstract: BackgroundLittle is known of how accurately a first-time seizure witness can provide reliable details of a semiology. Our goal was to determine how accurately first-time seizure witnesses could identify key elements of an epileptic event that would aid the clinician in diagnosing a seizure.MethodsA total of 172 participants over 17 years of age, with a mean (sd) of 33.12 (13.2) years and 49.4% female, composed of two groups of community dwelling volunteers, were shown two different seizure videos; one with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…[32] Witnesses tend to inaccurately describe movements, misleading medical professionals away from focal events. [33] Subtle features such as automatisms, lip movements or staring episodes are more difficult to identify, not just for lay persons but also healthcare professionals. [34] Different semiologies can be associated with different levels of reporting accuracy, with non-convulsive semiologies being less accurately described than convulsive events.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Witnesses tend to inaccurately describe movements, misleading medical professionals away from focal events. [33] Subtle features such as automatisms, lip movements or staring episodes are more difficult to identify, not just for lay persons but also healthcare professionals. [34] Different semiologies can be associated with different levels of reporting accuracy, with non-convulsive semiologies being less accurately described than convulsive events.…”
Section: Discussionmentioning
confidence: 99%
“…According to Botíková and Počuchová [9] findings, the awareness of the general public about EPI is high (80%). Another example is the research conducted by Muayqil et al [23], who found out that 71% of the overall number of 172 respondents from general public correctly identified epilepsy as the cause of the seizure. This also support Donáth and Čiernik [24] by their research, where 81% of patients treated for EPI think that the people around them are capable of providing them first aid during the epileptic seizure.…”
Section: Discussionmentioning
confidence: 99%
“…It is at this point where the eyewitnesses of the event play a fundamental role, since they are a valuable source of information that should be questioned in a cautious manner in order to describe the events that occurred. A study in 2018 managed to prove that regardless of age or educational level, people who witness a seizure event have a high level of accuracy in describing it [9]. A first seizure event should initially be classified as provoked or unprovoked; provoked seizures may be due to acute or remote symptomatic factors, including metabolic disorders, acute infections, drug toxicity or structural brain lesions.…”
Section: Clinical Considerationmentioning
confidence: 99%